The serpent's gift : gnostic reflections on the study of religion - Kripal, Jeffrey J. (Jeffrey John), 1962- (University of Chicago Press, 2007)
?Because thou hast done this, thou art cursed above all cattle, and above every beast of the field.? With those words in Genesis, God condemns the serpent for tempting Adam and Eve, and the serpent has shouldered the blame ever since. But how would the study of religion change if we looked at the Fall from the snake?s point of view? Would he appear as a bringer of wisdom, more generous than the God who wishes to keep his creation ignorant?. Inspired by the early Gnostics who took that startling view, Jeffrey J. Kripal uses the serpent as a starting point for a groundbreaking reconsideration of.